1991
DOI: 10.1177/074355489164002
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Costs and Benefits of Peer Relationships During Adolescence

Abstract: The purpose of this study was to examine gender differences in the impact of social stress and social support on adolescents' emotional well-being. Forty-eight males and 70 females in Grades 7 through 11 were administered a questionnaire containing scales measuring self-esteem, depression, social suppor4 and social stress. Females reported greater depression, lower self-esteem, and greater problem-focused support than did males. There were no significant differences in the amount of social stress or emotional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 24 publications
2
27
0
Order By: Relevance
“…Furthermore, a recent study showed that similar pat terns could be identified among adolescents. Adolescent girls gained somewhat fewer benefits (social support) and experienced substantially greater costs (social stress) than males, in their peer relationships (Moran & Eckenrode, 1991). The findings of the present study suggest that the greater susceptibility of females to the "contagion of stress" is related to their increased tendency to assume personal responsibility for the wel fare of others, a tendency that may be fostered and reinforced by tradi tional feminine roles.…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, a recent study showed that similar pat terns could be identified among adolescents. Adolescent girls gained somewhat fewer benefits (social support) and experienced substantially greater costs (social stress) than males, in their peer relationships (Moran & Eckenrode, 1991). The findings of the present study suggest that the greater susceptibility of females to the "contagion of stress" is related to their increased tendency to assume personal responsibility for the wel fare of others, a tendency that may be fostered and reinforced by tradi tional feminine roles.…”
Section: Discussionmentioning
confidence: 55%
“…Consequently, difficulties in interpersonal skill degrade self-esteem in women(34;35), placing them at greater risk for MDD(36–38). Men, on the other hand, are more likely to become depressed in response to status or occupational loss(39;40).…”
Section: Discussionmentioning
confidence: 99%
“…and Bentler (1992), Hollinger (1985), and Mullis and McKinley (1989) showed that self-esteem The Journul of' Genetic Psychology tively related to measures of masculinity/instrumentality. Moran and Eckenrode (1991) extended the work of Ouellet and Joshi (1986) by demonstrating the link between social support, social stress, and self-esteem among adolescent boys and girls. Knox, Funk, Elliott, and Bush (1996) investigated the relationship of "possible selves" (categories of self-concept) to global self-esteem and found that females' self-esteem is related to multiple domains of possible selves, whereas males' self-esteem is related to only one domain.…”
mentioning
confidence: 88%